DUMPING DALAM PERSPEKTIF HUKUM DAGANG INTERNASIONAL DAN HUKUM ISLAM (UINSI Samarinda, 2015)
This paper discusses the views of international commercial law and Islamic law against the practice of dumping. Dumping is the practice of selling a product in export destination countries at a price below the normal price which aims to dominate the market abroad. Dumping is often made by a country to capture the international market, so it is the case that is high figure in international trade. Indonesia is ranked five on charges of dumping. Dumping is the practice of dishonest trading, but the dumping was not prohibited by the WTO. Importing countries can apply anti-dumping duties against dumping of products to prevent or reduce the effects of serious losses on similar domestic products. Islam recognizes the term dumping by the term 'siyasah al-ighraq' or slam the price. In contrast to world trade law, Islam prohibits the dumping as in the provision of the Prophet hadith, because it will cause misery or bankruptcy of producers of similar goods.